Fitness Cost of Transgenic cry1Ab/c Rice Under Saline-Alkaline Soil Condition - Fu, Jianmei; Song, Xiaoling; Liu, Biao; Shi, Yu; Shen, Wenjing; Fang, Zhixiang; Zhang, Li (Frontiers in Plant Science, 2018)
The environmental release and biosafety of transgenic Bt crops have attracted global attention. China has a large area of saline-alkali land, which is ideal for large-scale production of Bt transgenic rice. Therefore an understanding of the fitness of Bt transgenic rice in saline-alkaline soils and the ability to predict its long-term environmental effects are important for the future sustainable use of these crops. In the present study, we aimed to evaluate the fitness of cry1Ab/c transgenic rice in both farmland and natural ecosystems. Transgenic cry1Ab/c rice Huahui1, for which a national biosafety certificate was obtained, was grown on normal farmland and saline-alkaline soils in a glass greenhouse. The expression pattern of exogenous Cry1Ab/c protein, and vegetative and reproductive fitness of rice were assessed. The expression of the exogenous Cry1Ab/c protein in the transgenic rice grown on saline-alkaline soil was lower than that in the strain grown on farmland soil. Under both the soil conditions, vegetative growth abilities, as evaluated by tiller number and biomass, and reproductive growth abilities, as measured by filled grain number and filled grain weight per plant, showed a significantly higher fitness cost for Huahui1 than that for the parental rice Minghui63 grown under the same soil conditions. In saline-alkaline soil, the fitness cost of Huahui1was moderately higher than that of Minghui63. Therefore, the ecological risk of cry1Ab/c transgenic rice is not expected to be higher than that of parental rice Minghui63 if the former escapes into natural saline-alkaline soil. The results of the present study provide a scientific basis to improve environmental safety assessment of the insect-resistant transgenic rice strain Huahui1 before commercialization.